Management of Online-Based Learning Media Through The Google Classroom Application in Increasing Student Learning Interest - Fathor Rozi; Saiful Rijal (STAI Terpadu Yogyakarta, 2023)
This study describes the application of managing online learning media through the Google Classroom application to increase student interest in MI Miftahul Islam. Media in daring learning is especially very influential on students' learning interest; we need a suitable press. This research uses a qualitative approach with a case study type. Data collection was carried out through direct observation and interviews. The informants in this study consisted of four people: the principal, the teacher, and two students. Data analysis was carried out through data collection, reduction, display, and drawing of conclusions. The study results found that management is carried out using; planning, implementing google classroom and evaluation. By implementing the direction of online learning media through the Google Classroom application, it can increase the learning interest of MI Miftahul Islam students supported by several factors, namely, (1) Ease of User Access, (2) Clear Exposure, (3) User Convenience, and (4) Interactive Communication. The implications obtained by managing google classroom learning media at MI Miftahul Islam can increase student learning interest marked by students' enthusiasm to participate in teaching and learning activities boldly.